Overlapping memberships on the audit and other board committees: impacts on financial reporting quality - Furqaan, Abdirahman; Annuar, Hairul Azlan; Hamdan, Hamdino; Abdul Rashid, Hafiz Majdi (Universiti Malaya, 2019)
Research aim: This research aims to investigate how overlapped members on the audit committee (AC) impact the primary role of the committee, especially in terms of improving the quality of the financial reporting of the company. Design/ Methodology/Approach: The population of the study consists of non-financial institutions listed on Bursa Malaysia (BM). Using purposive sampling, cross-sectional data were collected from the annual reports of the 100 top companies listed on BM. Research finding: The descriptive statistics of the study show that 98.7 per cent of the observed companies in this study have overlapping membership on the audit and other board committees. The study also shows that more than three-fourths of the AC members also serve on other board committees. The study found that overlapping memberships on the AC and other mandatory committees, significantly and positively impact the financial reporting quality (FRQ). Theoretical contribution/Originality: The results of this study suggest that overlapping memberships on the AC of the Malaysian big public listed companies play a significant role in terms of the FRQ of the company. Practitioner/Policy implication: Regulatory bodies and investors should encourage the chair of the AC to work on other board committees to bring relevant information to improve the performance of the AC. Research limitation/Implication: The inherent drawback of the current research is the small sample size, and that it does not provide in-depth and comprehensive data from the documents of the company. The research sample was drawn from the largest 100 Malaysian companies. Therefore, the results of the study may not be generalisable to smaller companies.